The Concussion Clinic: A Practical, Evidence-Based Model for Assessment and Management of Sport-Related Concussion - McCrea, M.; Powell, M. R. (Journal of Clinical Sport Psychology, 2012)
This article reviews the essential components of a practical, evidenced-based approach to the management of sport-related concussion in an ambulatory care setting. The model presented is based on the core philosophy that concussion assessment and management be approached from the biopsychosocial perspective, which recognizes the medical/physiological, psychological, and sociological factors that influence recovery and outcome following concussion. Based on the biopsychosocial paradigm, we outline a care delivery model that emphasizes an interdisciplinary approach in which the clinical neuropsychologist is a key participant. We discuss the importance of nonmedical, psychoeducational interventions introduced during the acute phase to facilitate recovery after sport-related concussion. Finally, using the local experience of our "Concussion Clinic" as a backdrop, we offer two separate case studies that demonstrate the value of this model in evaluating and managing athletes after sport-related concussion. The overall objective of this paper is to provide an adaptable template that neuropsychologists and other healthcare providers can use to improve the overall care of athletes with sport-related concussion and civilians with mild traumatic brain injury.